Bioaccessibility of phenolic compounds from Brazilian grape juices using a digestion model with intestinal barrier passage. (April 2023) - Dutra, Maria da Conceição Prudêncio; Martins da Silva, Ana Beatriz; de Souza Ferreira, Ederlan; Carvalho, Ana Julia de Brito Araujo; Lima, Marcos dos Santos; Telles Biasoto, Aline Camarão
Abstract: Grape juices are rich in bioactive compounds; however, for these compounds to exert their functionality, they must be bioaccessible. Thus, the present study evaluated a simulated digestion process on the main bioactive compounds of monovarietal grape juices of five Brazilian hybrid cultivars ( V. vinifera x V. labrusca ). Characterization of the chemical profiles in liquid chromatography (HPLC-DAD-RID), behaviour of phenolics in the stages of digestion and bioaccessibility through the INFOGEST protocol plus intestinal barrier passage were carried out. Of the 24 polyphenols identified in the grape juice samples, 11 were bioaccessible, with emphasis on the class of flavanols. Procyanidin B2 (101–426%), (+)-catechin (169–370%) and gallic acid (61–230%) stood out in all juices, showing that these compounds are key to the functionality of these drinks. Particularities were observed to differ between juices, demonstrating that factors such as the cultivar should be explored more extensively in studies on functional foods. The study also suggests that quality components such as sugars and organic acids influence the bioaccessibility of beverages.